Analisis Keberlanjutan Usaha Tani Jeruk Siam di Kecamatan Kuok Kabupaten Kampar Provinsi Riau - Nurhumairah, Nurhumairah; Edwina, Susy; Eliza, Eliza (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Siam orange farming (Citrus nobilis L.) plays a central role in the local economy of Riau. However, various challenges such as pest and disease attacks, market price fluctuations, and limitations in extension services and farmer groups can threaten the sustainability of this farming practice. This research aims to analyze the sustainability status of farming enterprises and identify the sensitive attributes of Siamese orange farming enterprises  A survey method was employed in this study, with a sample size of 30 respondents selected using the snowball sampling technique. Data collection was carried out using a questionnaire. Data analysis was performed using the multidimensional scaling (MDS) method with RAP-Orange software. The sustainability status of Siam orange farming in Kuok District is assessed as less sustainable with an index of 46.84. The ecological dimension is less sustainable with an index of 44.01, the economic dimension is moderately sustainable with an index of 64.30, and the social dimension is less sustainable with an index of 32.21. Sensitive attributes of the ecological dimension include land suitability, the intensity of pest and disease attacks, fertilizer usage levels, and pesticide usage levels. Sensitive attributes in the economic dimension include marketing chains, land ownership status, utilization of financial institutions/credit, ease of market access, price stability, and crop productivity levels. Sensitive attributes in the social dimension include participation in extension activities, community views on farming, farming information, education levels, and the intensity of extension activities.